IMPACT OF POSTURAL POSITION ON DETERMINATION OF AORTIC STIFFNESS AND CENTRAL BLOOD PRESSURE. (June 2022) - Philibert, Emy; Paré, Mathilde; Côté, Nadège; Fortier, Catherine; Duval, Karine; Goupil, Rémi; Obeid, Hasan; Agharazii, Mohsen
Abstract : Objective: Aortic stiffness is associated with increased central pulse pressure and cardiovascular disease and mortality. It is generally performed by determination of carotid-femoral pulse wave velocity (PWV) in a supine position. Two alternative approaches have been developed to estimate aortic stiffness, namely brachial pulse waveform analysis (Mobil-O-Graph) and finger-to-toe PWV by photoplethysmography (pOpmeter). These devices make it possible to assess and estimate aortic stiffness conveniently in different positions. However, it remains unclear if the values obtained are independent of the position at the time of measurement. Therefore, the aim of the present study is to determine the extent of postural changes on pulse wave velocity and central blood pressure estimation using pOpmetre and Mobil-O-Graph devices in a group of healthy controls. Design and method: Central blood pressure and PWV were assessed in 20 healthy subjects using both Mobil-O-Graph (PWV-M) and pOpmetre (PWV-pop) in three positions: supine position in bed, supine position in medical sampling chair and a sitting position. Central systolic blood pressure (SBP) was determined by calibration of brachial systolic and diastolic blood pressures (C1 calibration) by both methods (SBP-M and SBP-pop). Results: In the supine position in bed, PWV-M and PWV-pop were similar (5.5 ± 1.0 vs 5.4 ± 1.3 m/s, P = NS). In the supine position in a sampling chair, PWV-M decreased slightly (5.3 ± 1.0 m/s, P = 0.04 vs supine in bed), while PWV-pop increased significantly (5.9 ± 1.5 m/s, P = 0.04 vs supine in bed). However, in the sitting position, while PWV-M was not statistically different from the supine position (5.5 ± 1.0 m/s, P = NS), PWV-pop increased very significantly (9.2 ± 1.7 m/s, P < 0.001). Central blood pressure estimation remained similar for SBP-M (110.2 ± 10.3 vs 106.9 ± 10.5 vs 108.8 ± 11.1 mmHg, P = NS) and for SBP-pop (107.7 ± 10.4 vs 110.3 ± 9.6 vs 109.5 ± 9.9 mmHg, P = NS). Conclusions: These preliminary results tell us that postural position has little impact on the determination of aortic stiffness by the approach using brachial pulse wave analysis. However, finger-to-toe PWV increases remarkably with changes in position, possibly offering to explore the relationship between hydrostatic pressure and arterial stiffness as a dynamic test.